International Comparisons of Critical Thinking: Correcting Myths about Asian Students - Rear, David (University of Muhammadiyah Prof. DR. HAMKA, 2019)
One of the most important academic skills university students are expected to demonstrate is critical thinking. There is, however, a widespread view that, as a result of their cultural and educational backgrounds, students from east Asia find critical thinking particularly challenging. This paper critically examines this contention. It begins by analysing existing research on three broad themes: (1) cultural attitudes and dispositions towards critical thinking; (2) international comparisons of scores on critical thinking tests; (3) the impact of L1 and L2 use on academic performance. It also presents data from a study conducted by the author comparing the performance of Japanese students on a critical thinking task in their L1 and L2. It finds that, contrary to the accepted wisdom, there is little objective evidence to suggest Asian students are deficient in critical thinking in the broad sense of the term, either in disposition or ability. The lack of critical thinking skills apparently displayed by these students in Western contexts can largely be blamed on the issue of language proficiency. This finding has implications for academic skill courses in both EFL and ESL settings.